Development and User Experiences of a Biopsychosocial Interprofessional Online Course on Persistent Somatic Symptoms - van Gils, A.; Tak, L. M.; Sattel, H.; Rosmalen, J. G. M. (Frontiers in Psychiatry, 2021)
Background: Communication between healthcare providers and patients with persistent somatic symptoms (PSS) is frequently hampered by mutual dissatisfaction. We developed an online, interprofessional course to teach healthcare providers the knowledge, skills, and attitude they need to diagnose and treat PSS in a patient-centered manner. This paper describes the results of a study, assessing healthcare provider satisfaction and self-reported learning gains. Methods: The course consisted of six modules of 45 to 60 minutes. Each module contained different types of assignments including videos, discussion boards, reading assignments. We included healthcare providers (general practitioners, medical specialists, physiotherapists, nurses, and psychologists), following the course as continuing vocational training. Participants were asked to fill out online surveys about their learning gains and satisfaction with the course. Results: In total, 801 participants started the course; participants included mostly general practitioners, physiotherapists and mental healthcare workers. At the start of the course, 22% of the participants rated their level of knowledge on PSS as adequate. At the end of the course, 359 participants completed the evaluation questionnaires. Of this group, 81% rated their level of knowledge on PSS as adequate and 86% felt that following the course increased their competencies in communicating with patients with PSS. On a scale from 1 to 10, participants gave the course a mean grade of 7.8 points. Conclusions: According to healthcare providers, this online, interprofessional course is an effective and satisfying way to learn about PSS. Observer- and, in particular, patient-rated outcomes are to be studied in the future.